Analisis Intensi Muzakki dalam Membayar Zakat Profesi - Huda, Nurul; Gofur, Abdul (Al-Iqtishad: Journal of Islamic Economics, 2012)
The aims of this research is to determine the influence of attitude, subjective norm, behavioral control, muzakki incomen, muzakki education, and muzakki knowledge to the muzakki intention of paying profession zakah. The method of the research is a quantitative method while data analysis techniques use multiple regression analysis. Number of samples analyze are 150 respondents drawn at random from all areas of Jakarta. Based on multiple regression analysis, it can be seen that the variables together attitudes, subjective norms, behavior control, income, education, and knowledge has significant influence on the variable of muzakki intentionDOI: 10.15408/aiq.v4i2.2098